2009
DOI: 10.2138/am.2009.3000
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of tetrahedrally coordinated Al and B in tourmaline: An 11B and 27Al MAS NMR study

Abstract: Considerable uncertainty has surrounded the occurrence of tetrahedrally coordinated Al and B at the T site in tourmaline. Although previously detected in several tourmaline specimens, the frequency of these substitutions in nature, as well as the extent to which they occur in the tourmaline structure, is not known. Using 11 B and 27 Al MAS NMR spectroscopy, we have investigated the presence of B and Al at the T site in 50 inclusion-free tourmaline specimens of low transition-metal content and different species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 40 publications
(48 reference statements)
4
40
0
Order By: Relevance
“…Ertl and Hughes (2002) even schorls, and with a high olenite component can contain significant [4] B. This was corroborated by MAS NMR investigations of magnesiofoitite (Lussier et al 2009), which did not show [4] B. However, Marschall et al (2004), based on structural investigations of a metamorphic dravite from Syros, Greece, concluded that 'substantial contents of Mg at the Y site or at the Z site do not exclude the possibility of the occurrence of [4] B'.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Ertl and Hughes (2002) even schorls, and with a high olenite component can contain significant [4] B. This was corroborated by MAS NMR investigations of magnesiofoitite (Lussier et al 2009), which did not show [4] B. However, Marschall et al (2004), based on structural investigations of a metamorphic dravite from Syros, Greece, concluded that 'substantial contents of Mg at the Y site or at the Z site do not exclude the possibility of the occurrence of [4] B'.…”
Section: Resultsmentioning
confidence: 78%
“…Consequently, a structural study with the use of the Rietveld method could not be done. Magic-anglespinning nuclear magnetic resonance (MAS-NMR) spectroscopy, commonly applied for detecting [4] B and [4] Al in tourmaline (Tagg et al 1999;Marler and Ertl 2002;Lussier et al 2009), also cannot be applied due to the very high presence of paramagnetic Fe ions. Lussier et al (2009) did show that a high content of paramagnetic ions results in a dramatic decrease of intensity, and the recorded spectra are illegible.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Since a substantial amount of B-at the T-site ( [4] B) was determined through the structural refinement and chemical analysis of olenite (Ertl et al, 1997;Hughes et al, 2000), 11 B magic-angle-spinning nuclear magnetic resonance spectroscopy has been applied frequently to estimate the fraction of [4] B at the T-site in the 'Mashuroom' tourmaline sample from Myanmar (e.g., Ertl et al, 2007;Lussier et al, 2008aLussier et al, , 2008bLussier et al, , 2009Lussier et al, , 2011. Therefore, it may be interesting to discuss the site population of the T-site by using the information on occupation parameters, unit formulae calculated from chemical analysis, and mean bond length.…”
Section: Resultsmentioning
confidence: 99%
“…The tetrahedron can also be occupied by B (e.g. Ertl et al 2002a, 2006, 2007, 2015Hughes et al 2004;Lussier et al 2008Lussier et al , 2009Kutzschbach et al 2016Kutzschbach et al , 2017.…”
Section: Cationic Sitesmentioning
confidence: 99%